Effects of bolus doses of fat on small intestinal structure and on release of gastrin, cholecystokinin, peptide tyrosine-tyrosine, and enteroglucagon. Issue 2 (February 1992) - Jenkins, A P; Ghatei, M A; Bloom, S R; Thompson, R P
Abstract : To investigate the enterotrophic effects of bolus doses of long chain triglycerides, two groups of eight female Wistar rats were fed identical diets with 48.2% total calories as the essential fatty acid rich oil Efamol. To one group the oil was given in twice daily bolus doses by gavage, while for the other group the oil was mixed with the remainder of the feed and thus consumed over 24 hours. The animals were killed after 20 to 22 days. Bolus dosing significantly increased parameters of mucosal mass along the length of the small intestine in association with an increase in two hour accumulation of vincristine arrested metaphases in small intestinal crypts. In a second experiment, four replicate studies were carried out, each involving two groups of 12 rats respectively fed as described above. After 21 days one animal from each group was killed every two hours, providing regular plasma samples over 24 hours for measurement of gastrin, cholecystokinin, peptide tyrosine-tyrosine and enteroglucagon. Bolus dosing markedly enhanced release of peptide tyrosine-tyrosine and enteroglucagon, but not of gastrin or cholecystokinin. Thus, the enhanced enterotrophic effects of bolus doses of long chain triglycerides could be mediated by release of a distally located gut peptide, perhaps enteroglucagon.